Total severity score and age predict long-term hospitalization in COVID-19 pneumonia - Nasoufidou, Athina; Kavelidou, Marianthi; Griva, Theodora; Melikidou, Eleni; Maskalidis, Charalampos; Machaira, Konstantina; Nikolaidou, Barbara (Frontiers in Medicine, 2023)
BACKGROUND: COVID-19 severe pneumonia implies increased oxygen demands and length of hospitalization. We aimed to assess a possible correlation between admission’s clinical-laboratory data, including the total severity score (TSS) from chest computed tomography (CT) with the hospitalization time among COVID-19 patients. METHODS: Data files were assessed retrospectively at the General Hospital "Agios Pavlos" in Greece. Clinical-laboratory data, TSS and duration of hospitalization were recorded. RESULTS: 317 patients, 136 women and 181 men, with a mean age of 66.58±16.02 years were studied. Significant comorbidities were hypertension (56.5%), dyslipidemia, (33.8%), type 2 diabetes (22.7%), coronary heart disease (12.9%), underlying pulmonary disease (10.1%) and malignancy (4.4%). Inpatient time was related to age (p<0.001), TSS (p<0.001), time from symptom onset to hospitalization (p=0.006), inhaled oxygen fraction (p<0.001), fibrinogen (p=0.024), d-dimers (p<0.001) and C-reactive protein (p=0.025), and with a history of hypertension (p <0.001) and type 2 diabetes mellitus (p<0.008). The multivariate analysis showed significant association of the inpatient duration with age (p<0.001) and TSS (p<0.001) independently of the above factors. CONCLUSION: Approaching early the disease severity with TSS and patients’ age, is useful for the inpatient resource allocation, and to maintain vigilance for those at risk for long hospitalizations.